Types of Social Participation among the Elderly in Bandung City, Indonesia - Sharon Gondodiputro; Yusuf Naufal Athaya Fauzan; Anggraini Widjajakusuma (Faculty of Medicine, Universitas Padjadjaran, 2026)
Elderly individuals are at increased risk of experiencing various health problems associated with isolation and loneliness. Social participation with family, friends, neighbors, and engagement in community activities has been proven to reduce these risks. This study aimed to identify the types of social participation activities undertaken by elderly residents in Bandung City, Indonesia. A quantitative descriptive study was conducted involving 100 elderly individuals who visited Community Health Centers in Bandung City, using multistage purposive convenience sampling. The study variables were respondent characteristics and types of social participation at the family, friend, neighbor, and community levels.The most common forms of social participation with family and neighbors involved direct conversations. Religious activities and cleaning up the neighborhood (kerja bakti in local language) were the most frequently reported types of social participation with neighbors and the broader community. Based on these findings, it is necessary to develop various structured and easily accessible community activities to provide the elderly with more opportunities for meaningful social participation.